MAKNA GURU DALAM KONSEP TA’LIM, TARBIYYAH DAN TAZKIYYAH - Wawan Setiawan (Jurnal Pendidikan Islam, 2013)
This paper intends to analyze concepts associated to the duties and functions of a teacher such as, tarbiyyah, and tazkiyyah in al-Quran based on philosophical and pedagogical. There are a number of new challenges to interpret these concepts in order contextual with the demands and needs of the times. The results showed that the study groups is not just imparting knowledge and skills, but also emphasize the empowering sense. Empowering mind will enable students to develop skills in solving everyday problems. Empowering mind can deliver students aware of God's wisdom. Orientation tarbiyyah intends to develop the potential of physical, psychological, and affective concerns such as moods, feelings, self-image, motivation, mental toughness as a characteristic ribbiyyûn. Tazkiyyah aims to develop heart as a place of faith, and avoiding polytheism. The activity was done by planting a religious duty to practice the habit of the practice of worship with the appreciation will be God's wisdom.